2020
DOI: 10.1021/acs.inorgchem.9b03557
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight on Defect-Rich Tin Oxide for Smart Band Alignment Engineering and Tunable Visible-Light-Driven Hydrogen Evolution

Abstract: Herein, a series of defect-rich tin oxides, Sn x O y , were synthesized with tunable Sn2+/Sn4+ composition ratio and defect chemistry, aiming to explore the impact of local structural modulation, non-stoichiometric chemistry, and defective center on the modulation of band gap values, band edge potential positions, and photocatalytic hydrogen evolution performance. The phase structure, morphology, surface component, and photoelectric properties were analyzed by multiple testing methods. The modulation of the Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The existence of these two peaks can be assigned to the angular vibration of the O−Sn−O bond and the stretching vibration of the Sn−O bond, respectively, which is a typical SnO 2 characteristic peak [21] . With the increase of Sn 2+ , the above two peaks obviously merge into a single peak located at 630 cm −1 , which confirms that the Sn−O bond (503 cm −1 ) is converted from terminal bond to bridging bond (630 cm −1 ) [20] . The broad and weak infrared absorption bands appear around the 800–1250 cm −1 and are enhanced with the increase of Sn 2+ concentration.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The existence of these two peaks can be assigned to the angular vibration of the O−Sn−O bond and the stretching vibration of the Sn−O bond, respectively, which is a typical SnO 2 characteristic peak [21] . With the increase of Sn 2+ , the above two peaks obviously merge into a single peak located at 630 cm −1 , which confirms that the Sn−O bond (503 cm −1 ) is converted from terminal bond to bridging bond (630 cm −1 ) [20] . The broad and weak infrared absorption bands appear around the 800–1250 cm −1 and are enhanced with the increase of Sn 2+ concentration.…”
Section: Resultsmentioning
confidence: 82%
“…The broad and weak infrared absorption bands appear around the 800–1250 cm −1 and are enhanced with the increase of Sn 2+ concentration. These absorption bands are considered as electronic transitions from the intrinsic donor level to the tin dioxide sample conduction band, indicating that the doped sample has very abundant oxygen vacancies [20,22] . The absorbance peak near 3577 cm −1 in the spectra is attributed to the O−H stretching vibration of adsorbed water molecules and a peak around 1619 cm −1 is the H−O−H bending deformation vibration of free water molecules [23] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…), surface/interface chemistry, electronic structure, and morphological structure of semiconductor, and it has been found that these inherent properties have a great influence on the photocatalytic activity of semiconductor. [6] This is very important to design and develop high efficient semiconductor photocatalytic materials.…”
Section: Introductionmentioning
confidence: 99%